2009
DOI: 10.1186/ar2584
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among type I and type II interferon, tumor necrosis factor, and β-estradiol in the regulation of immune response-related gene expressions in systemic lupus erythematosus

Abstract: IntroductionSystemic lupus erythematosus (SLE) is a prototypical autoimmune disease characterized by various clinical manifestations. Several cytokines interact and play pathological roles in SLE, although the etiopathology is still obscure. In the present study we investigated the network of immune response-related molecules expressed in the peripheral blood of SLE patients, and the effects of cytokine interactions on the regulation of these molecules.MethodsGene expression profiles of peripheral blood from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…Previous studies showed repressive effect of TNF-alpha on interferon-inducible gene expression [37,38], and the inverse correlation between TNF-alpha and IFN-alpha in HC should be a consequence of their cross regulation. However, unlike in HC, TNF-alpha may fail to regulate IFN-alpha production in SLE, and a combined increase of both cytokines can promote the pathogenesis [39].…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies showed repressive effect of TNF-alpha on interferon-inducible gene expression [37,38], and the inverse correlation between TNF-alpha and IFN-alpha in HC should be a consequence of their cross regulation. However, unlike in HC, TNF-alpha may fail to regulate IFN-alpha production in SLE, and a combined increase of both cytokines can promote the pathogenesis [39].…”
Section: Discussionmentioning
confidence: 90%
“…16 Therefore, the possibility that E 2 plays a significant role in the pathophysiology of SLE cannot be excluded. 17 There is little information in the medical literature about a relationship between serum IFN-g, vitamin D, and E 2 levels in female SLE patients of reproductive age with inactive disease. Due to the known effects of these factors on the course of lupus disease and in order to better understand the etiopathogenesis of SLE, we explored the relationship between these factors specifically in patients with inactive disease to minimize confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported increased expression of IFN-inducible genes (that is, the 'IFN signature') in peripheral blood cells from patients with SLE [2-4]. Many groups are currently looking into pathological roles of plasmacytoid dendritic cells (pDCs) and IFN-inducible genes in SLE since pDCs are major producers of IFN-α [4-7].…”
Section: Interferon Signaturementioning
confidence: 99%